USA-1 IS EXEMPLARY AUTOMATIZED SPECTROMETER FOR EXPRESS-ANALYSIS OF METALS AND ALLOYS - V. Ju. Stetsenko; N. I. Gilkov; V. A. Usova (Литьë и металлургия)
New standard spectral analyzer for express-analysis of metals and alloys is presented.